Pengaruh Investment Opportunity Set Dan Biaya Agency Terhadap Kebijakan Dividen Dengan Posisi Kas Sebagai Varibel Pemoderasi (Studi Pada Perusahaan Manufaktur Di Bursa Efek Indonesia) - Laila Wardani; Muhammad Ahyar; Iwan Kusuma Negara (Universitas Mataram, 2022)
The research aims is to acknowledge the influence of opportunity set which is represented by market to book value of equity ratio (MVE) ratio of property plant and equipment to firm value (PPE) and price earning ratio (PER) and agency cost which represented by the ownership of institutional on dividend policy with the cash position as moderating variable, this is a quantitative research data collecting method use sample survey while data collecting technique done by documentation, number of sample is taken from ten manufacture companies which listed at BEI and analysis device is conducted trough multiple regression. Research result shows that market to book value of equity ratio (MVE) and ratio of property plant and equipment to firm value (PPE) have significant influence on dividend payout ratio while price earnings ratio and the ownership of institutional have no significant influence on dividend payout ratio, later the cash position could moderate the influence of ratio of property plant and equipment to firm value (PPE) and price earning ratio (PER) on dividend payout ratio, the cash position could not moderate the influence of market to book value of equity ratio (MVE) and the ownership of institutional on dividend payout ratio